Noise control material using jute (Corchorus olitorius): effect of bulk density and thickness. Issue 1 (2nd January 2021) - Sengupta, Surajit; Basu, Gautam; Datta, Mallika; Debnath, Sayandeep; Nath, Devarun
Abstract: An attempt has been made to study the effect of thickness and compactness of natural fibre assembly in the reduction of noise. Fourteen available natural fibres i.e. banana, bhimal, roselle, coconut, cotton, wool, flax, hemp, jute, nettle, okra, pineapple, ramie, sisal and two synthetic sound absorbers i.e. rockwool, glass wool have been tested for sound absorption coefficient. Depending on availability and sound absorbency property, jute fibre ( Corchorus olitorius ), has been selected for detailed study. Test probe has been designed to test the fibre bundle in impedance tube principle. It is observed that there are significant absorption and transmission loss of sound energy through the jute fibre bundle either alone or covered with paper laminate. Statistical models based on second-order standard polynomial and Box and Benken factorial design, have been suggested to predict the sound transmission loss and absorption with respect to thickness and density in different frequency level of sound for stuffed fibre and paper panel stuffed with fibre. The correlation coefficients between observed and predicted values are above 0.95. Stuffed jute fibre shows maximum sound absorption with 30 mm thickness, 1.0 g/cm 3 density in the application of 5000 Hz sound frequency. In case of transmission loss for below 18 mm thickness, jute fibre stuffed paper laminate panel shows increase up to 1.0 g/cm 2 and then decrease. The sound loss reaches the maximum in the application of 1500 Hz frequency and then remains constant. Therefore, it can be effectively used as sound absorber or barrier protecting the environment from sound pollution, if designed properly. The knowledge from this study can help to design sound insulator or barrier from an industrial crop like jute.